IMPROVING STUDENTS’ READING COMPREHENSION THROUGH SKIMMING AND SCANNING TECHNIQUE IN TEACHING NARRATIVE TEXT - Doni Lesmana; Iwan Supardi; Yanti Sri Rezeki (Universitas Tanjungpura, 2019)
AbstractThis study was carry out to improve the students reading comprehension of narrative text through skimming and scanning technique on eighth grade students of SMP Mujahidin Pontianak in academic year 2018/2019. The subjects of this study were consisted of 21 students. The method used in this study was classroom action research (CAR). The classroom action research design applied in this study was a collaborative classroom action research. It meant that the writer collaborated with the English teacher of SMP Mujahidin Pontianak as an observer and collaborator. This study was conducted following Kurt Lewin model with the following procedures of the action research: planning, acting, observing, and reflecting. The study was carry out in two cycles. Each cycle consisted of two meetings. The data were gathered in this study through interview, field notes, and test. Most of the students gradually gained good scores at the end of the cycle. The score of Minimum Mastery Criterion- Kriteria Ketuntasan Minimal (KKM) of English lesson was 75 (seventy-five). The mean in the first cycle was 70,1. The mean score in the second cycle was 75,4. In conclusion, Skimming and Scanning technique could improve students’ reading comprehension.Keywords: Classroom Action Research, Narrative text, Reading comprehension